2001
DOI: 10.1093/ajcn/74.3.387
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a 4-y, high-fiber, high-fruit-and-vegetable, low-fat dietary intervention: results of dietary changes in the Polyp Prevention Trial

Abstract: Motivated, free-living individuals, given appropriate support, can make and sustain major dietary changes over a 4-y period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
151
0
4

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(160 citation statements)
references
References 43 publications
5
151
0
4
Order By: Relevance
“…However, given the errors associated with self-reported dietary intake measuring instruments, lifestyle interventions may report substantial changes in self-reported dietary intake that are not reflected in biomarker change (33,34). The WHEL Study achieved significant increases in carotenoid concentration at 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…However, given the errors associated with self-reported dietary intake measuring instruments, lifestyle interventions may report substantial changes in self-reported dietary intake that are not reflected in biomarker change (33,34). The WHEL Study achieved significant increases in carotenoid concentration at 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…Recruitment activities occurred at eight U.S. clinical centers, starting in the spring of 1991 and ending in January 1994. More detailed descriptions of the exclusion criteria (22), dietary intervention (17,23), and trial results (16) are reported elsewhere.…”
Section: Methodsmentioning
confidence: 99%
“…According to food frequency data, the difference in intakes for the three trial dietary goals in the intervention and control groups at the end of the 4-year trial was À9.7% (FSE) of calories (23.8 F 0.2 in the intervention group; 33.9 F 0.2 in the control group), +6.9 g fiber/1,000 kcal (17.4 F 0.2 in the intervention group; 10.0 F 0.1 in the control group), and +1.13 servings of fruits and vegetables/1,000 kcal (3.41 F 0.04 in the intervention group; 2.23 F 0.03 in the control group; ref. 17). Despite these differences in diet, there was no difference in adenoma recurrence.…”
Section: Introductionmentioning
confidence: 94%
“…In some trials, the control group did not receive any intervention which raises questions about study validity [41,46,47]. The majority of the identified interventions had no theoretical basis, and most of them used traditional methods of education such as individual/group counseling or printed material, and most did not achieve a significant change in dietary behaviour [4045,48]. Whilst a few studies have reported change in one or another dietary behaviour using information technology tools most had one of the methodological flaws mentioned above [40,49,50,51].…”
Section: Discussionmentioning
confidence: 99%